2016
DOI: 10.1089/end.2015.0393
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Hernia Repair During Extraperitoneal Robot-Assisted Laparoscopic Radical Prostatectomy

Abstract: Unilateral and bilateral TEP added operative time to RALP but had equivalent outcomes to both LRP+TEP and RALP alone. This is likely due to the similar surgical space used for RALP and TEP, which obviates the need for substantial further dissection. For men with prostate cancer and comorbid IH, combined RALP+TEP appears to be an appropriate surgical combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 15 publications
1
10
1
1
Order By: Relevance
“…Ludwig et al (6) report that 33% of patients scheduled to undergo radical prostatectomy have concomitant inguinal hernia. Additionally, another study that investigated the incidence of inguinal hernia following prostate surgery, reports that the incidence rate of inguinal hernia after radical prostatectomy, open prostatectomy, and transurethral resection of the prostate (TUR-P) was 23.9%, 18.9%, and 2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ludwig et al (6) report that 33% of patients scheduled to undergo radical prostatectomy have concomitant inguinal hernia. Additionally, another study that investigated the incidence of inguinal hernia following prostate surgery, reports that the incidence rate of inguinal hernia after radical prostatectomy, open prostatectomy, and transurethral resection of the prostate (TUR-P) was 23.9%, 18.9%, and 2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, simultaneous repair of groin hernia can always be repaired quickly and easily. Therefore, groin hernia repair has rapidly gained popularity in the past decade, especially during a robot‐assisted radical prostatectomy, which potentially increases the incidence of groin hernias after surgery . However, whether we really need a surgical robot just for repairing a simple groin hernia is still questionable due to its higher cost, longer operative time, and uncertainty about its clinical benefits …”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic groin hernia repairs are commonly carried out via two standard approaches, either trans‐abdominal pre‐peritoneal (TAPP) repair or total extra‐peritoneal (TEP) repair. In the robotic era, most of the reported robot‐assisted techniques were performed using the TAPP approach, except in very limited case reports of simultaneous TEP repair during a robot‐assisted radical prostatectomy . Although these two standardized laparoscopic approaches for groin hernia repair are comparable in their long‐term clinical outcomes, the TAPP approach was associated with more surgical complications and seroma formation than was the TEP approach in a large‐scale population‐based study …”
Section: Introductionmentioning
confidence: 99%
“…The hernia sac was reduced, and the synthetic mesh was used to reinforce the myopectineal orifice. When compared to standard LRP or RARP, unilateral TEP prolonged operative time by approximately 30 min . Since IH recurrence was not observed, the authors concluded that RARP with concomitant TEP is safe, effective, and comparable to the laparoscopic approach.…”
Section: Preventive Measures From Open Surgery To Robotic Surgerymentioning
confidence: 96%
“…When compared to standard LRP or RARP, unilateral TEP prolonged operative time by approximately 30 min. 24 Since IH recurrence was not observed, the authors concluded that RARP with concomitant TEP is safe, effective, and comparable to the laparoscopic approach. Thus, simultaneous IH repair during RARP may be justified in patients with IH or subclinical IH.…”
Section: Ih Development After Rpmentioning
confidence: 98%